Stylasterid corals build aragonite skeletons in undersaturated water despite low pH at the site of calcification - Joseph A. Stewart; Ivo Strawson; James Kershaw; Laura F. Robinson (Scientific Reports, 2022)
Abstract Anthropogenic carbon emissions are causing seawater pH to decline, yet the impact on marine calcifiers is uncertain. Scleractinian corals and coralline algae strongly elevate the pH of their calcifying fluid (CF) to promote calcification. Other organisms adopt less energetically demanding calcification approaches but restrict their habitat. Stylasterid corals occur widely (extending well below the carbonate saturation horizon) and precipitate both aragonite and high-Mg calcite, however, their mode of biocalcification and resilience to ocean acidification are unknown. Here we measure skeletal boron isotopes (δ11B), B/Ca, and U/Ca to provide the first assessment of pH and rate of seawater flushing of stylasterid CF. Remarkably, both aragonitic and high-Mg calcitic stylasterids have low δ11B values implying little modification of internal pH. Collectively, our results suggest stylasterids have low seawater exchange rates into the calcifying space or rely on organic molecule templating to facilitate calcification. Thus, despite occupying similar niches to Scleractinia, Stylasteridae exhibit highly contrasting biocalcification, calling into question their resilience to ocean acidification.